2012
DOI: 10.1371/journal.pone.0042963
|View full text |Cite
|
Sign up to set email alerts
|

Negative Priming in a Joint Selection Task

Abstract: Recent studies have suggested that the observation of another individual executing a movement activates representations of the observed movement in the observer. These representations are thought to be used by other systems to facilitate a variety of social cognitive processes, such as social searches. Previous research on social searches has primarily involved contexts where targets were presented in isolation. Typical environments, however, contain targets and non-targets and one must select the correct info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 25 publications
2
12
1
Order By: Relevance
“…If knowledge and co-representation of a co-actor’s task influences the mechanisms associated with the joint attentional blink, then a joint attentional blink will emerge. Such a finding would be consistent with the studies suggesting that knowledge and co-representation may lead to other social attention effects such as social IOR ( Welsh et al, 2005 ) and negative priming ( Welsh and McDougall, 2012 ). A joint attentional blink effect should emerge if the partner responding to T2 co-represents and simulates the performance of their partner who identifies T1.…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…If knowledge and co-representation of a co-actor’s task influences the mechanisms associated with the joint attentional blink, then a joint attentional blink will emerge. Such a finding would be consistent with the studies suggesting that knowledge and co-representation may lead to other social attention effects such as social IOR ( Welsh et al, 2005 ) and negative priming ( Welsh and McDougall, 2012 ). A joint attentional blink effect should emerge if the partner responding to T2 co-represents and simulates the performance of their partner who identifies T1.…”
Section: Introductionsupporting
confidence: 91%
“…This simulation leads to the same interference effects that emerge as though the individual performed the task on their own [see also Welsh et al (2005) for a similar account of the social IOR effect]. In support of the hypothesis that the same mechanisms are activated on individual and joint trials, Welsh and McDougall (2012) reported that the magnitude of the negative priming effect on individual and joint trials was significantly correlated (see also Welsh et al, 2009 ). Overall, the results of the joint negative priming and social IOR studies provide evidence in favor of the hypothesis that co-actors maintain a representation of their partner’s task and may engage in a simulation of their partner’s performance when they observe that selection, even when it is temporally distinct and independent from their own task.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations